A systematic review of clinical applications and diagnostic efficacy of intravascular optical coherence tomography in cardiology - Sacoto, Vanessa Marisol Almeida; Mite, Ana Paula Coronel; Pilatasig, Washington Javier Masapanta; Mosquera-Ceprian, Rafael Andres; Cunduri, Edith Viviana Muñoz; Castillo, Angelica Marina Basantes; Roldán, Víctor Manuel Polo; Saltos, Juan José Martínez; Barzallo, Jorge Andres Rivera; Herrera, Santiago Israel Cárdenas (International Journal of Research in Medical Sciences, 2024)
Intravascular Optical Coherence Tomography (OCT) has emerged advanced imaging modality in cardiology, offering high-resolution visualization of coronary artery structures. Since its inception in the late 1990s, OCT has undergone significant advancements, transitioning from time-domain to frequency-domain systems, thereby enhancing its clinical viability and diagnostic efficacy. We aimed to comprehensively assess the clinical applications and diagnostic efficacy of intravascular OCT in cardiology, particularly in guiding percutaneous coronary interventions (PCI) and evaluating coronary artery diseases. In methodology, A systematic search was conducted in PubMed and Google Scholar databases for studies published between 2013 and 2023, comparing OCT with intravascular ultrasound (IVUS) and conventional angiography (C.A.) in guiding PCI procedures. Studies were selected based on predefined inclusion and exclusion criteria, focusing on major adverse cardiovascular events (MACE), cardiac death, and revascularizations as outcomes. In results we included 28 studies from databased and 3 manuals, highlighting OCT’s superior resolution in identifying thin-capped fibroatheromas (TCFAs), optimizing stent placement, and assessing plaque composition. Comparative analyses revealed no significant differences in clinical efficacy between OCT and IVUS, with both modalities showing superiority over C.A. in reducing cardiovascular events. The OCTIVUS trial further confirmed the non-inferiority of OCT-guided PCI compared to IVUS-guided PCI, with lower procedural complications reported in the OCT group. In conclusion, Intravascular OCT has revolutionized the diagnostic and interventional landscape in cardiology, offering unparalleled insights into coronary artery pathology. Its high-resolution imaging capabilities facilitate accurate plaque characterization, stent optimization, and real-time intervention guidance, thereby improving clinical outcomes in PCI procedures. Future research should focus on expanding OCT’s applications and further validating its efficacy in diverse clinical settings.